(untitled) - Swick, Ed (New York, 2005)
This new addition to the Practice Makes Perfect series makes it easier than ever for ESL learners to get the hang of English pronouns and prepositions. In clear, straightforward language, and with the help of numerous everyday examples, language teacher Ed Swick demystifies English pronouns and prepositions, and he provides dozens of skill-building exercises. The numerous exercises include a variety of formats, such as fill-in-the-blank sentences, sentence rewriting, writing original sentences, and more.
Keywords: English language; Grammar